Research progress and perspective on lithium/sodium metal anodes for next-generation rechargeable batteries - Patrike, Apurva; Yadav, Poonam; Shelke, Vilas; Shelke, Manjusha (ChemSusChem, 2022)
With the development of consumer electronic devices and electric vehicles, lithium-ion batteries (LIBs) are vital components for high energy storage with great impact on our modern life. However, LIBs still cannot meet all the essential demands of rapidly growing new industries. In pursuance of higher energy requirement, metal batteries (MBs) are the next-generation high-energy-density devices. Li/Na metals are considered as an ideal anode for high-energy batteries due to extremely high theoretical specific capacity (3860 and 1165 mAh g(-1) for Li and Na, respectively) and low electrochemical potential (-3.04 V for Li and -2.71 V for Na vs. standard hydrogen electrode). Unfortunately, uncontrolled dendrite growth, high reactivity, and infinite volume change induce severe safety concerns and poor cycle efficiency during their application. Consequently, MBs are far from commercialization stage. This Review represents a comprehensive overview of failure mechanism of lithium/sodium metal anode and its progress for rechargeable batteries through (i) electrolyte optimization, (ii) artificial solid-electrolyte interphase (SEI) layer formation, and (iii) nanoengineering at materials level in current collector, anode, and host. The challenges in current MBs research and potential applications of lithium/sodium metal anodes are also outlined and summarized.
Keywords: anode; Batteries; dendrite growth; Electrolytes; Energy storage